2021
DOI: 10.1155/2021/8891373
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Reduces Oxidative Stress and Neuronal Apoptosis via the ERK/Nrf2/HO‐1 Pathway after Intracerebral Hemorrhage in Rats

Abstract: Background. Albumin has been regarded as a potent antioxidant with free radical scavenging activities. Oxidative stress and neuronal apoptosis are responsible for its highly damaging effects on brain injury after intracerebral hemorrhage (ICH). Here, the present study investigated the neuroprotective effect of albumin against early brain injury after ICH and the potential underlying mechanisms. Methods. Adult male Sprague-Dawley rats were subjected to intrastriatal injection of autologous blood to induce ICH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Secondary nerve damage after ICH is mainly due to mitochondria-dependent neuronal apoptosis caused by continuous oxidative stress ( Duan et al, 2016 ), and various antioxidant cellular pathways may become new therapeutic targets to rescue neurons and promote functional nerve restoration during ICH treatment ( Righy et al, 2016 ). In recent years, several studies have demonstrated that curcumin can promote the recovery of neurological function after ICH by inhibiting intracranial oxidative stress and regulating redox balance ( Xie et al, 2020 ; Deng et al, 2021 ). Potent antioxidant drugs can effectively inhibit the rapidly increasing ROS during the early stage of ICH, thereby inhibiting neuronal necrosis ( Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary nerve damage after ICH is mainly due to mitochondria-dependent neuronal apoptosis caused by continuous oxidative stress ( Duan et al, 2016 ), and various antioxidant cellular pathways may become new therapeutic targets to rescue neurons and promote functional nerve restoration during ICH treatment ( Righy et al, 2016 ). In recent years, several studies have demonstrated that curcumin can promote the recovery of neurological function after ICH by inhibiting intracranial oxidative stress and regulating redox balance ( Xie et al, 2020 ; Deng et al, 2021 ). Potent antioxidant drugs can effectively inhibit the rapidly increasing ROS during the early stage of ICH, thereby inhibiting neuronal necrosis ( Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3,4-dihydroxyphenylethanol may be a powerful agent in the treatment of EBI after SAH because of its free radical scavenging capacity and modulating the Akt and NF-κB signaling pathway ( Zhong et al, 2016 ; Fu and Hu, 2016 ). In addition to the intervening abovementioned diseases, other drugs commonly used clinically, such as heparin ( Hayman et al, 2017 ), albumin ( Deng et al, 2021 ), and propofol ( Zhang H. B. et al, 2019 ), all projected an antioxidative role. Some authors believe that preconditioning would provide the greatest chance of benefit but is obviously not effective ( Mayor et al, 2013 ; Zolnourian et al, 2019 ; Ruan et al, 2020 ; Otsuka et al, 2021 ).…”
Section: Oxidative Stress In Early Brain Injurymentioning
confidence: 99%
“…OSA aggravates EBI via the ATF4/CHOP signaling pathway following ICH. deng et al (39) reported that the aTF4/cHoP signaling pathway is a key mechanism by which brain injury is ameliorated in icH rats. Therefore, the present study investigated whether OSA aggravated apoptosis and neuroinflammation by regulating the aTF4/cHoP signaling pathway.…”
Section: Osa Further Increases Expression Levels Of Apoptosisassociated Proteins Following Ichmentioning
confidence: 99%